Anthelmintic Resistance, Validation of FAMACHA and Effects of Management Practices in Selected Goat Farms in Terengganu, Malaysia. - Abdul Aziz, Nor Azlina (2010)
A total of 230 goats from six goat farms in Marang, Kuala Berang and Setiu, Terengganu were chosen for this study. Distribution of anthelmintic resistance is reported to be widespread in Malaysia. Therefore, it is important to evaluate the present anthelmintic resistance status f goats in Terengganu. Fecal samples were taken for fecal egg count (FEC). From 230 goats, 141 goats were chosen for detection of resistance by using Fecal Egg Count Reduction test, using levamisole, ivermectin, benzimidazole and closantel with each group having at least five goats including control. All farms had resistance towards benzimidazole and closantel while only two farms were still susceptible to levamisole nd one farm had suspected resistance to ivermectin. There were four out of six farms that has resistance to all anthelmintics tested. The strongyles which had developed anthelmintic resistance were were predominantly ahsrmonchus contortus followed by Trachostrongylus spp. Results obtained from this study showed that anthelmintic resistance is escalating and the need for effective action is very important for the small ruminant industry. Due to importance of helminthiasis in small ruminant industry, a quick, easy and useful field diagnostic method have developed in South Africa which is known as FAMACHA© eye color chart. The ocular mucous membrane of sheep and goats are classified by comparison with a laminated color chart bearing pictures of conjunctiva classified into five categories ranging from normal red through pink to practically white in severe anemia. Before the chart can be implemented to be use in this country, it is important to validate the system. Eye color based on FAMACHA© grading, blood and fecal samples were taken and subjected to packed cell volume (PCV) and FEC respectively. Two separate FAMACHA© scores defined as anemia were ≥ 3 and ≥ 4. The correlation between PCV and FAMACHA© eye score, and PCV and FEC were highly significant (P<0.01), but the correlation between FEC and FAMACHA© eye score were not significant. Sensitivity was 100% when FAMACHA© scores of 3 and above were considered and anemic, while specificity increased (63.08%) when FAMACHA© scores of 4 and above were considered as anemic. The data obtained strongly suggest that FAMACHA© method is a valuable diagnostic tool for identifying anemic goats. Due to widespread anthelmintic resistance, other options need to be investigated besides chemical control. Good management practices has been reported to reduce worm burden and reduces the frequency of anthelmintic use. Therefore, it is important to study the effect of some management practices to control helminthiasis. The practices chosen were grazing time, mineral block supplementation, type of drug used, breed, source of animal, additional feed and drenching personnel. Data on management practices adopted by the six farms were obtained from a survey based on a questionnaire. Worm burden was extrapolated from fecal egg counts (FEC). The data analysis was done by systematic using t-test, Spearman correlation and ANOVA. Afternoon grazing reduced the mean FEC nearly five-fold compared to morning grazing and mineral block supplementation reduced FEC two-fold compared to unsupplemented goats (P<0.05). Anthelmintic resistance in Terengganu is alarmingly increasing and this is a big threat to small ruminant production. FAMACHA© is a useful technique to diagnose anemia cause by J. contortus. By selective treatment, it will reduces anthelmintic frequency, thus delays the resistance development management practices is an important option for controlling parasitism in small ruminant.